Legend in Belarusian and Chinese folklore: theoretical and methodological aspects of genre identification and classification - Xun, Zhang (Journal of the Belarusian State University. Philology, 2025)
From the perspective of Belarusian and Chinese aesthetic paradigms, the article examines the specifics of the legend genre, its historical poetics and dynamics of change, relationship with myth, classification. A conclusion is made about different strategies of integration and interaction of folklore genres within the framework of these cultural and historical conditions. The Belarusian tradition is characterised by a sequential change of narratives (the model myth - legend - fairy tale) towards a decrease in sacredness and an increase in the fictional nature of the narrative. In Chinese culture, mythological and legendary narratives coexist and have equal axiological and conceptual-discursive status. It is suggested that the genres of legend emerge sequentially (from mythological to historical and socio-utopian). The mythological legend actualises the plot, character and figurative structure of the myth in new conditions.